genotype - environment interaction in new plant type (npt) lines of rice (oryxa sativa L) - Marimutthu M (Department of Plant Breeding and Genetics, College of Horticulture, 2007)
The present study on Genotype - Environment interaction in New Plant Type (NPT) lines of rice was carried out in the Department of Plant Breeding & Genetics, College of Horticulture, Kerala Agricultural University, Vellanikkara.